Relative multi-beneficial effect of MOs on plant health of chickpea (Cicer arietinum L. var. PG-186) - Tomer, Supriya; Khati, Priyanka; Suyal, Deep Chandra; Perveen, Kahkashan; Khan, Faheema; Barasarathi, Jayanthi (Frontiers in Microbiology, 2024)
The phosphate solubilizing properties of Lysinibacillus macroides ST-30, Pseudomonas pelleroniana N-26, and Bacillus cereus ST-6 were tested for the chickpea crop of the Tarai region of Uttarakhand. These microbially inoculated plants have shown significant (p > 0.05) improvement in the plant health and crop health parameters, viz., root length, shoot length, fresh weight, dry weight, nodule number, nodule fresh weight, nodule dry weight, chlorophyll content, and nitrate reductase. The highest shoot length (46.10 cm) and chlorophyll content (0.57 mg g−1 fresh weight) were observed in ST-30 at 75 DAS with 20 kg P2O5/ha. Similarly, for plant P content, an increase of 90.12% over control was recorded in the same treatment. Treatments consisting of Lysinibacillus macroides ST-30 along with 20 kg/ha P2O5 were found to be most suitable as phosphatic fertilizer. Conclusively, sustainable agriculture practices in the Tarai as well as the field region may be developed based on a strategy of exploring microbial inoculants from the pristine region of the Western Himalayas. The presence and abundance of bacterial inoculants were confirmed through qRT-PCT. We conclude that the effective plant growth-promoting bacterium Lysinibacillus macroides ST-30 broadens the spectrum of phosphate solubilizers available for field applications and might be used together with 20 Kg/ha P2O5.